ANALISIS KESALAHAN SISWA KELAS VII SMP KATOLIK REGINA PACIS AIRMADIDI DALAM MENYELESAIKAN SOAL CERITA OPERASI HITUNG BILANGAN BULAT - Raymond Pesik; James U.L. Mangobi; Miftahul Jannah (Universitas Nias Raya, 2026)
The high rate of student mistakes in working through integer operation word problems formed the basis of this investigation. Solving word problems demands that learners comprehend the scenario, convert it into a mathematical representation, and execute computations correctly. The present study set out to map the categories of mistakes committed by students and trace their root causes through the lens of Newman’s Error Analysis framework. A descriptive qualitative methodology was applied throughout the research. Thirteen Grade VII students of SMP Katolik Regina Pacis Airmadidi served as research participants. Data were gathered via written examinations and follow-up interviews, then processed using the Miles and Huberman interactive model. Findings revealed an absence of reading errors across all participants. Encoding errors emerged as the most prevalent mistake type (60%), with process skills errors (47.69%), transformation errors (32.30%), and comprehension errors (30.76%) following in sequence. The aggregate error rate reached 34.15%. Contributing factors included insufficient grasp of problem content, careless computation particularly involving negative integers difficulty converting narrative problems into mathematical expressions, and unfamiliarity with structured solution writing. It is recommended that teachers cultivate students’ habit of recording systematic, step-by-step solutions and deepening their conceptual understanding of integer operations.